2015
DOI: 10.1016/j.ijid.2015.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Brucellosis in pregnancy: clinical aspects and obstetric outcomes

Abstract: This is the largest series of brucellosis in pregnancy reported in the literature. Brucella presents adverse obstetric outcomes including fetal and maternal/neonatal death. Cases with unexplained spontaneous abortion should be investigated for brucellosis. Prompt treatment is paramount to decrease the devastating outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
78
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(84 citation statements)
references
References 22 publications
2
78
0
Order By: Relevance
“…It is important to remember that Brucella can be transmitted by breast-feeding, thus exposed/infected mothers should take caution with their newborns. Neonatal Brucella infection is associated with bacteremia and acute diseases associated with organ dysfunction and respiratory distress 16,17 . Cutaneous lesions have been reported in patients with Brucella infection, as nodules, papules, erythema, and petechial.…”
Section: Clinical Findingsmentioning
confidence: 99%
“…It is important to remember that Brucella can be transmitted by breast-feeding, thus exposed/infected mothers should take caution with their newborns. Neonatal Brucella infection is associated with bacteremia and acute diseases associated with organ dysfunction and respiratory distress 16,17 . Cutaneous lesions have been reported in patients with Brucella infection, as nodules, papules, erythema, and petechial.…”
Section: Clinical Findingsmentioning
confidence: 99%
“…Pappas et al [11] and Gustavo et al [4] found more sacro-ileitis in the subacute phase. Genital and urinary complications come second [4]. In addition, hematological disorders have been described in pregnant women, mainly anemia [9,10,11].…”
Section: Observationmentioning
confidence: 94%
“…According to Elshamy the incidence of this infection in pregnant Saudi women extends to 12.2% [1]. A new study published in 2015 by Gustavo et al found an average of 2.3 cases per year [4].…”
Section: Observationmentioning
confidence: 99%
See 2 more Smart Citations